2020
DOI: 10.3389/fmats.2020.00035
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electrical Behaviors of Apatite, Dolomite, Quartz, and Phosphate Ore

Abstract: The phosphate ore flotation is achieved through the surface electrical behavior difference among apatite, dolomite and quartz, but it is usually affected by the dissolved ions from pulp, especially Ca 2+ and Mg 2+ . The zeta potentials of apatite, dolomite, quartz, and phosphate ore in different solutions were measured to discuss the surface electrical behaviors of them in this study. It was found that the apatite, dolomite and phosphate ore supernatants have limited impact on the zeta potentials of the respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The ZP analysis shows consistent results with the state of the art based on the dependence on the variation in the pH of the colloidal solution fluid, as presented by several authors [20,21,43,59]. Moreover, the ZP analysis exhibited consistent trends with α quartz structures (Qz) predominant in the white representative fraction under study, with no isoelectric points (IEP) and more negative values with the increase in pH in the whole range from 3.0 to 11.0 [60,61]. Moreover, the values obtained in the study of the ZP showed negative values between −12 mV and −19mV under increasingly acidic conditions (pH 5.0) and more negative values with the increase in pH (concentration of OH − ) up to 11, as presented in Figure 7.…”
Section: Sisupporting
confidence: 86%
“…The ZP analysis shows consistent results with the state of the art based on the dependence on the variation in the pH of the colloidal solution fluid, as presented by several authors [20,21,43,59]. Moreover, the ZP analysis exhibited consistent trends with α quartz structures (Qz) predominant in the white representative fraction under study, with no isoelectric points (IEP) and more negative values with the increase in pH in the whole range from 3.0 to 11.0 [60,61]. Moreover, the values obtained in the study of the ZP showed negative values between −12 mV and −19mV under increasingly acidic conditions (pH 5.0) and more negative values with the increase in pH (concentration of OH − ) up to 11, as presented in Figure 7.…”
Section: Sisupporting
confidence: 86%
“…Thus, zeta potentials were measured to study the surface charges of dolomite and fluorapatite samples, and the results are listed in Figure . The isoelectric point (IEP) of pure fluorapatite was between pH 5.0–6.0, while that of dolomite was also around pH 6.0–7.0, consistent with previous studies. , It can be seen from Figure that the addition of NaOL caused a significant shift in the potential at the same pH, indicating that NaOL had adsorbed on the surfaces of dolomite and fluorapatite. The potential became more negative in the presence of NaOL, and was also higher than that without NaOL.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 85% of phosphorus resources in China can be classified as middle-low grade phosphate ore . Typically, this ore contains various gangue minerals such as dolomite, quartz, calcite (Sis and Chander, 2003;Zhou et al, 2020). As a result, the direct utilization of the raw phosphate ore is hindered.…”
Section: Introductionmentioning
confidence: 99%